2011
DOI: 10.1093/hmg/ddr435
|View full text |Cite
|
Sign up to set email alerts
|

Modeling abnormal early development with induced pluripotent stem cells from aneuploid syndromes

Abstract: Many human diseases share a developmental origin that manifests during childhood or maturity. Aneuploid syndromes are caused by supernumerary or reduced number of chromosomes and represent an extreme example of developmental disease, as they have devastating consequences before and after birth. Investigating how alterations in gene dosage drive these conditions is relevant because it might help treat some clinical aspects. It may also provide explanations as to how quantitative differences in gene expression d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 39 publications
6
56
0
Order By: Relevance
“…1F). This indicated that X chromosome aneuploidy does not affect reprogramming to pluripotency or differentiation into the three primary germ layers, similar to a previous report of iPSC-derived teratoma formation with Turner lines33.…”
Section: Resultssupporting
confidence: 89%
“…1F). This indicated that X chromosome aneuploidy does not affect reprogramming to pluripotency or differentiation into the three primary germ layers, similar to a previous report of iPSC-derived teratoma formation with Turner lines33.…”
Section: Resultssupporting
confidence: 89%
“…Human stem cell studies suggest that pseudoautosomal and other XCI escaping genes may have an important role in placental functions and early development [Urbach and Benvenisty, 2009;Li et al, 2012;Bellott et al, 2014]. This explains the 70-99% lethality of non-mosaic 45,X human embryos [Urbach and Benvenisty, 2009;Berletch et al, 2010;Hook and Warburton, 2014] as well as the almost complete unviability of X monosomy in species with large PARs [Raudsepp et al, 2012].…”
Section: The Functions Of Par Genesmentioning
confidence: 99%
“…Such discrimination might be important because recent studies in human embryonic and induced pluripotent stem cells show that functional diploidy for the PAR genes might be critical for normal embryonic development [Urbach and Benvenisty, 2009;Li et al, 2012]. That is why we carried out a pilot study profiling the expression of the PAR and X-specific genes in pigs.…”
Section: Expression Analysis Of the Pig Par And X-specific Genesmentioning
confidence: 99%
“…Initial evidence for this was provided by the studies of human XX and XO embryonic stem cells showing that XO cells which are haploinsufficient for the PAR and other genes that escape X inactivation, are differentially expressed in placenta [Urbach and Benvenisty, 2009]. Very recently, another human study used induced pluripotent stem cells (iPSCs) from XO individuals to model abnormal early development [Li et al, 2012] and showed that cell lines derived from XO iPSCs display lower expression level of PAR genes than normal controls. Indirectly, these findings are supported by the observations that viable XO individuals can be found in species with small PARs (human, horse, mouse) but are rare or absent in species with large PARs (pig, cattle, dog, cat) [Raudsepp et al, 2012], as if haploinsufficiency for too many PAR genes causes embryonic lethality.…”
Section: Functional Profiles Of Pig Par Genes In Adult and Embryonic mentioning
confidence: 99%
See 1 more Smart Citation